2020
DOI: 10.3389/fmed.2020.00226
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Algorithm for Use of Melatonin in Patients With COVID-19

Abstract: The coronavirus, COVID-19, has infected hundreds of thousands and killed tens of thousands of individuals worldwide. This highly infectious condition continues to ravage the world population and has yet to reach it peak infective rate in some countries. Many conventional drugs including hydroxychloroquine/chloroquine, lopinavir, remdesivir, etc., have been repurposed as treatments for this often deadly disease, but there is no specifically-designed effective drug available; also, the drugs mentioned have signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 56 publications
0
120
0
Order By: Relevance
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In transplant recipients with COVID-19, depression, anxiety, and sleep disturbances associated with COVID-19 can worsen non-adherence to immunosuppressive therapy and increase the risk of allograft rejection [ 58 ]. Melatonin is an effective drug for anxiety and sleep disturbances, which might also be beneficial for clinical outcomes of patients with COVID-19 due to its anti-inflammatory and anti-oxidant properties [ 59 , 60 ].…”
Section: Outpatient Management For Transplant Recipientsmentioning
confidence: 99%
“…The uncontrolled innate immune response promotes a massive inflammatory reaction and causes irreversible tissue damage and mortality. 5,6 Our group recently published a review on how the various medical comorbidities (diabetes mellitus, hypertension, obesity, and cardiovascular disease) can affect the melatonergic pathway and its relationship with COVID-19. In addition, we suggest melatonin doses for treatment and prophylactic use.…”
Section: To the Editormentioning
confidence: 99%
“…In addition, we suggest melatonin doses for treatment and prophylactic use. 6 When a vaccine is developed, it may not be as effective in elderly patients. A limited immune response to vaccines has been previously reported in older patients due to immunosenescence.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation